Rekayasa Piutang oleh Kreditor untuk Memenuhi Persyaratan Permohonan Pernyataan Pailit - Muhammad Redha Anshari (Lex Renaissance, 2016)
To meet the requirements of the bankruptcy proposal is with the existence of two or more creditors. However, there is a creditor that does not have a legal document known as the fictive creditor. The issues in this research included first; what is meant by fictive creditor? Second, how is the regulation of fictive creditor? This is a normative research in which the results of the research concluded that first, the fictive creditor is a creditor that does not have any valid document and the existence if none but emerged for certain purpose by the creditor or debtors themselves. Second, if this occurs the fictive creditor can be deceived with the articles on the falsification as regulated in Criminal Code. Those provisions are related to the issue of the letters not containing the truth or letters are adulterated as regulated in Chapter XII entitled “Tentang Pemalsuan Surat” (About the Letter Forgery), particularly Article 263, 264, and 266. There is one article 520 related to PKPU.  Keywords: Fictive creditor, bankruptcy and forgery